2018
DOI: 10.2337/dc17-1732
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Acute-to-Chronic Glycemic Ratio at Admission in Acute Myocardial Infarction: A Prospective Study

Abstract: In AMI patients with diabetes, A/C glycemic ratio is a better predictor of in-hospital morbidity and mortality than glycemia at admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
97
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 34 publications
11
97
0
1
Order By: Relevance
“…Instead of ABG, both glycaemic gap and SHR were associated with major adverse cardiac events (MACEs) and could provide moderate predictive value for the occurrence of MACEs in AMI patients with DM [15,22,34]. Liao et al further demonstrated glycaemic gap rather than ABG was linked to all-cause mortality in acute heart failure (AHF) patients with DM [35].…”
Section: Discussionmentioning
confidence: 99%
“…Instead of ABG, both glycaemic gap and SHR were associated with major adverse cardiac events (MACEs) and could provide moderate predictive value for the occurrence of MACEs in AMI patients with DM [15,22,34]. Liao et al further demonstrated glycaemic gap rather than ABG was linked to all-cause mortality in acute heart failure (AHF) patients with DM [35].…”
Section: Discussionmentioning
confidence: 99%
“…Panel D: Kaplan-Meier survival curves stratified by hs-CRP cut-off value (2 mg/L) and adjusted HR and 95% CI associated with a hs-CRP value ≥ 2 mg/L. All analyses were adjusted for left ventricular ejection fraction (≤ or > 40%), estimated glomerular filtration rate (≤ or > 60 ml/min/1.73 m 2 ), type of acute myocardial infarction (STEMI vs. NSTEMI) and prior statin use condition than those without DM [25], and this may, at least in part, explain their higher short-term and longterm mortality risk [26,27]. However, whether hs-CRP during AMI carries a different prognostic relevance in DM and non-DM patients is still a controversial issue.…”
Section: Inflammation and Dm In Amimentioning
confidence: 99%
“…Especially during hospitalization, it is a strong predictable factors for fatal outcomes in patients with AMI [5,17]. But A/C glycemic ratio was reported to be a better predictor of in-hospital morbidity and mortality than glycaemia at admission [3]. And positive correlation of serum HbA1c with the presence of carotid plaque [1] and vulnerable plaque in ACS were reported in previous studies [16].…”
Section: Discussionmentioning
confidence: 88%